2020
DOI: 10.1111/jac.12458
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between hydrogen peroxide and nitric oxide mediates priming‐induced drought tolerance in wheat

Abstract: Drought is a limiting factor for wheat production. Nitric oxide (NO) and hydrogen peroxide (H2O2) are key signalling molecules produced in response to drought stress. Drought priming is a promising strategy for enhancing drought tolerance. Here, the roles of NO and H2O2 in drought priming were investigated. The results showed that the scavengers of NO or H2O2 reduced the effects of priming‐induced tolerance to drought stress during seedling and grain filling stages. Drought priming induced the production of H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Together, they modulate the accumulation of osmolytes, regulate ABA-induced antioxidant enzyme activities, induce stomatal closure, protect mesophyll cell ultrastructure, and improve photosynthesis [ 99 , 100 , 101 , 102 ]. When priming the wheat seedlings with NO and H 2 O 2 , Wang et al [ 99 ] found that the tolerance level of pretreated wheat seedlings was enhanced. The accumulation of proline and glycine betaine was also increased [ 99 ].…”
Section: No and Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, they modulate the accumulation of osmolytes, regulate ABA-induced antioxidant enzyme activities, induce stomatal closure, protect mesophyll cell ultrastructure, and improve photosynthesis [ 99 , 100 , 101 , 102 ]. When priming the wheat seedlings with NO and H 2 O 2 , Wang et al [ 99 ] found that the tolerance level of pretreated wheat seedlings was enhanced. The accumulation of proline and glycine betaine was also increased [ 99 ].…”
Section: No and Drought Stressmentioning
confidence: 99%
“…When priming the wheat seedlings with NO and H 2 O 2 , Wang et al [ 99 ] found that the tolerance level of pretreated wheat seedlings was enhanced. The accumulation of proline and glycine betaine was also increased [ 99 ].…”
Section: No and Drought Stressmentioning
confidence: 99%
“…This phenomenon was also indicated by other authors under salt stress 55 . Priming T. aestivum seedlings with NO and H 2 O 2 resulted in improved drought tolerance and elevated accumulation of osmolytes 19 . On the other hand, in LDT genotypes of both species a decreased content of H 2 O 2 was observed in the analyzed conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, its production can also be promoted by NO 18 . Both particles can be associated with a regulation of osmolytes content, ABA-induced activity of antioxidant system, stomatal movement and improve photosynthesis 19 22 . NO under stress conditions might act also as ROS scavenger which minimizes their harmful effects on plant metabolism 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent report showed that higher Pro accumulation as a result of drought hardening in wheat seedlings ( T. aestivum Yangmai 16) induced by two subsequent periods of polyethylene glycol treatment was dependent on NO (Wang et al . 2021), whose bioactivity is exerted mainly through PTMs, such as S‐nitrosation (Begara‐Morales et al . 2018).…”
Section: Discussionmentioning
confidence: 99%